Cerebrovascular Dysfunction in Atrial Fibrillation - Junejo, Rehan T.; Lip, Gregory Y. H.; Fisher, James P. (Frontiers in Physiology, 2020)
It is now well established that besides being the most common cardiac arrhythmia, atrial fibrillation is a major healthcare burden. Risk of debilitating stroke is increased in atrial fibrillation patients, but even in the absence of stroke this population is at heightened risk of cognitive decline, depression and dementia. The reasons for this are complex, multifactorial and incompletely understood. One potential contributing mechanism is cerebrovascular dysfunction. Cerebral blood flow is regulated by chemical, metabolic, autoregulatory, neurogenic and systemic factors. The dysfunction in one or more of these mechanisms may contribute to the elevated risk of cognitive decline and cerebrovascular events in atrial fibrillation. This short review presents the evidence for diminished cerebral blood flow, cerebrovascular carbon dioxide reactivity (i.e., cerebrovascular vasodilatory reserve), cerebral autoregulation and neurovascular coupling in atrial fibrillation patients when compared to control participants in sinus rhythm. Further work is needed to understand the physiological mechanisms underpinning these observations and their clinical significance in atrial fibrillation patients.